The Emerging Role of Tetraspanins in the Proteolytic Processing of the Amyloid Precursor Protein - Seipold, Lisa; Saftig, Paul (Frontiers in Molecular Neuroscience, 2016)
Tetraspanins are a family of ubiquitously expressed and conserved proteins, which are characterized by four transmembrane domains and the formation of a short and a large extracellular loop (LEL). Through interaction with other tetraspanins and transmembrane proteins such as growth factors, receptors and integrins, tetraspanins build a wide ranging and membrane spanning protein network. Such tetraspanin-enriched microdomains (TEMs) contribute to the formation and stability of functional signaling complexes involved in cell activation, adhesion, motility, differentiation, and malignancy. There is increasing evidence showing that the tetraspanins also regulate the proteolysis of the amyloid precursor protein (APP) by physically interacting with the APP secretases. CD9, CD63, CD81, Tspan12, Tspan15 are among the tetraspanins involved in the intracellular transport and in the stabilization of the gamma secretase complex or ADAM10 as the major APP alpha secretase. They also directly regulate, most likely in concert with other tetraspanins, the proteolytic function of these membrane embedded enzymes. Despite the knowledge about the interaction of tetraspanins with the secretases not much is known about their physiological role, their importance in Alzheimer's Disease and their exact mode of action. This review aims to summarize the current knowledge and open questions regarding the biology of tetraspanins and the understanding how these proteins interact with APP processing pathways. Ultimately, it will be of interest if tetraspanins are suitable targets for future therapeutical approaches.